Volcanic rocks proceedings of the International Workshop on Volcanic Rocks, Workshop W2 : 11th Congress ISRM, Ponta Delgada, Azores, Portugal, 14-15 July 2007 - International Workshop On Volcanic Rocks, Workshop W2 2007 Ponta Delgada, Azores); Malheiro, Ana Maria; Nunes, João Carlos (London Taylor & Francis, 2019)
Environmental issues are high on the public agenda and engineering projects need to take environmental concerns on board. Volcanic Rocks, contains papers from the ISRM Workshop W2 (Ponta Delgada, Azores, Portugal 14-15 July 2007), and focuses specifically on problems associated with construction activities in areas of volcanic rock.
Electronic reproduction.
Keywords: Volcanism -- Congresses; Rock mechanics -- Congresses